Management of Coalescence of the Little Lips in Girls at the Pediatric Surgery Department of the Donka National Hospital (HND) of the Conakry Chu (London Journal of Medical and Health Research, 2024)
Introduction: Coalescence of the labia minora, also called coalescence of the nymphs, is an acquired pathology of prepubescent little girls. It is relatively common but poorly understood by practitioners. The objective of this study is to report the management of this pathology in our African social conditions. Patients and methods : We carried out a retrospective descriptive study of the files of child patients aged less than 15 years treated for coalescence of the labia minora in the pediatric surgery department over a period of 5 years. The epidemiology, diagnosis, therapeutic and evolutionary aspects were studied. Results: We collected 28 files of coalescence of the labia minora and the annual incidence was 5.6 cases per year. The average age of our patients was 13 months with a range of 4 months and 2 years 9 months. Twenty-four (85.72%) were less than 2 years old. The circumstances of discovery were made by the mother at home by chance in 24%. The main reason for consultation was spontaneous vaginal closure. In the history we noted a case of perineal erythema and a urinary infection. In this study there were 20 cases of total form coalescence and 8 cases of partial form. All patients were asymptomatic. Surgical detachment was done with the Halsted forceps (22 cases) and by the thermometer (6 cases). Local antiseptic care and 72 hours of oral antibiotic therapy were prescribed for all patients. Five patients were given an adjunct to a prescription for estrogen-based colpotrophin ointment. The postoperative course was simple. After a 1-year follow-up, no recurrence was found in our study. Conclusion: Coalescence of the labia minora remains an acquired and benign pathology in little girls. Surgical detachment under local anesthesia in a single attempt in our social context remains the only effective treatment.
Keywords: Insomnia; zolpidem; and side effects.; Nonunion; recalcitrant; allograft; humeral fractures.; malnutrition; sarcopenia; advanced cancer; palliative care; home care; Osteochondroma. Osteochondromatosis. Bone neoplasms.; treatment; Coalescence of the labia minora; Vulva; Little girl